Job Satifaction Among Civil Servants: How Organizational Culture And Work Environment Inspire Performance - Anggoro KR., M. Yusuf Alfian Rendra (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
This study analyzes the determining factors for job satisfaction and performance among Civil Servants in Indonesia. The data were analyzed from 380 responses by using the AMOS-SEM. The results showed that organizational culture, work environment, and job satisfaction positively and significantly affect the apparatus's performance in all direct relationships. Indirect relationships are partially significant, illustrating that the better and superior construction of better state management requires specific approaches to increase the expected outcomes.